Perovskite quantum dot photovoltaic materials beyond the reach of thin films: Full-range tuning of a-site cation composition - Hazarika, A; Zhao, Q; Gaulding, E; Christians, J; Dou, B; Marshall, A; Moot, T; Berry, J; Johnson, J; Luther, J (American Chemical Society, 2018)
We present a cation-exchange approach for tunable A-site alloys of cesium (Cs+) and formamidinium (FA+) lead triiodide perovskite nanocrystals that enables the formation of compositions spanning the complete range of Cs1–xFAxPbI3, unlike thin-film alloys or the direct synthesis of alloyed perovskite nanocrystals. These materials show bright and finely tunable emission in the red and near-infrared range between 650 and 800 nm. The activation energy for the miscibility between Cs+ and FA+ is measured (∼0.65 eV) and is shown to be higher than reported for X-site exchange in lead halide perovskites. We use these alloyed colloidal perovskite quantum dots to fabricate photovoltaic devices. In addition to the expanded compositional range for Cs1–xFAxPbI3 materials, the quantum dot solar cells exhibit high open-circuit voltage (VOC) with a lower loss than the thin-film perovskite devices of similar compositions.